Delayed-Type Hypersensitivity Reaction to Red Tattoo Ink Triggered by Ledipasvir/Sofosbuvir for Hepatitis C: A Case Report - Meghan L. McPhie; Kevin Y.M. Ren; J. Michael Hendry; Sonja Molin; Thomas Herzinger (Karger Publishers, 2021)
Tattoos have become increasingly popular worldwide making adverse effects from tattoos a growing concern. In our report, we present a 51-year-old man who developed an unusual allergic reaction to the red ink portions of his tattoos that coincided with the initiation of ledipasvir/sofosbuvir treatment for his hepatitis C. Clinical and histological features were consistent with a delayed-type hypersensitivity reaction to red ink.